ETHNOBOTANY STUDY OF TRADITIONAL COMMUNITY MEDICINE FOR BATAK TRIBE IN LAWE PERBUNGA, BABUL MAKMUR SUB-DISTRICT, SOUTHEAST ACEH - Yanti, Alprida; Kriswiyanti, Eniek; Darmadi, A. A. Ketut (SIMBIOSIS; Vol 10 No 2 (2022)DO - 10.24843/JSIMBIOSIS.2022.v10.i02.p02, 2022)
Traditional medicine is a mixture of natural ingredients that have been used for generations for treatment based on experience which is inherited from their ancestors. Traditional medicine systems are generally closely related to religious aspects and also use natural elements such as plants, animals, and minerals. One of the people who still use traditional medicine is the Batak tribe in Lawe Perbunga, Babul Makmur Sub-district, Southeast Aceh. This study aims to examine the types of plants, plant parts used, processing methods and the use of traditional medicines is the Batak tribe in Lawe Perbunga, Babul Makmur Sub-district, Southeast Aceh. The method used in this research is purposive sampling and snowball to determine 40 respondents. Data collection techniques used interviews, observation, documentation and literature study. Data analysis used qualitative and quantitative descriptive analysis techniques. The types of plants used as ingredients for traditional medicinal consist of 21 species and 18 family for the treatment of 20 types of diseases. The plant parts used as medicinal ingredients, respectively, were leaves, fruit, tubers, rhizomes, sap, stems and roots respectively 48,39%, 12,90%, 12,90%, 9,68%, 6,45%, 6,45%, and 3,23%. Processing of traditional medicinal ingredients in 5 ways, namely without being processed, boiled, sliced, brewed and roasted, respectively, by 43,75%, 20,31%, 20,31%, 9,38% and 6,25%.The use of traditional medicine are carried out in 4 ways, namely drinking, eating, smearing, and affixing respectively 45,59%, 29,41%, 17,65% and 7,35%. Keywords: Lawe Perbunga Village, use, processing, medicinal plants